Cell Wall Synthesis, Development of Hyphae and Metabolic Pathways Are Processes Potentially Regulated by MicroRNAs Produced Between the Morphological Stages of Paracoccidioides brasiliensis - de Curcio, Juliana S.; Paccez, Juliano D.; Novaes, Evandro; Brock, Mathias; Soares, Célia Maria de Almeida (Frontiers in Microbiology, 2018)
MicroRNAs are molecules involved in post-transcriptional gene regulation. In pathogenic fungi, microRNAs have been described at different morphological stages by regulating targets involved in processes such as morphogenesis, energy production. Members of the Paracoccidioides complex are the main etiological agents of a systemic mycosis in Latin America. Fungi of the Paracoccidioides complex present a wide range of plasticity to colonize different niches. In response to environmental changes these fungi undergo a morphological switch, remodel their cellular metabolism and modulate structural cell wall components. However, the underlying mechanisms regulating gene expression have hardly been understood. By using high performance sequencing and bioinformatics analyzes this work characterizes microRNAs produced by Paracoccidioides brasiliensis. Here, we demonstrate that transcripts encoding proteins involved in microRNA biogenesis are differentially expressed in each morphological stage. In addition, 49 microRNAs were identified in cDNA libraries with 44 differentially regulated among the libraries. 16 microRNAs were differentially regulated in the comparison of mycelium with the mycelium-to-yeast transition phase. The yeast parasitic phase revealed a complete remodeling of the expression of these small RNAs. Analyses of targets of the induced microRNAs from the different libraries revealed that these molecules may potentially regulate the in the cell wall by repressing genes involved synthesis and degradation of glucans and chitin. Furthermore, mRNAs involved in cellular metabolism and development of were predicted as regulated by microRNAs. Therefore, this work describes a putative post regulation mediated by microRNAs in P. brasiliensis and its influence on the adaptive processes of this thermal dimorphic fungus.